Prevalencia de endoparásitos y ectoparásitos en caninos (canis lupus familiaris) de la parroquia de Cusubamba - Aguinsaca Palacios, Deysi Paulina (2021)
This research was carried out in the Parish of Cusubamba in the Province of Cotopaxi, based on determining the prevalence of endoparasites and ectoparasites in domestic canines (canis lupus familiaris), by coproparasitic analysis for endoparasites, drawer test and skin scrapings for ectoparasites, to structure preventive measures against zoonotic parasitic diseases. The coproparasitic technique that was put into practice was Sheather's, the technique that was applied for direct observation of ectoparasites, was the drawer test and use of endectocide talc, the total number of animals sampled was 200 of which the following results were obtained: positive animals to endoparasites 121, that represent 61% and the remaining 79 canines that correspond to 39%, Ancylostoma spp. 39.69% Dipylidium spp. 6.23%, Strongylus spp. 9.16%, trichuris spp. 5.29% of toxocara spp. 0.18% and isospora spp. 39.41%. In the prevalence by age groups, it was shown that the group with the highest prevalence were geriatrics with a prevalence of 43.5% with Ancylostoma spp. 46.89%, Dipylidium spp. 6.47%, Strongylus spp. 6.99%, trichuris spp. 3.88% and isospora spp. 35.75%; Adults with a prevalence of Ancylostoma spp 36.22%, Dipylidium spp 9.88%, Strongylus spp 12.87%, Trichuris spp 3.88% and isospora spp 35.75%; puppies with Ancylostoma spp 36.17%, Dipylidium spp 1.76%, Strongylus spp 10.88%, Trichuris spp 8.23%, Toxocara spp 0.29% and isospora 42.64%; In the prevalence of endoparasites according to sex, it was identified in males Ancylostoma spp 35.32%, Dipylidium spp 5.60%, Strongylus spp 10.59%, Trichuris spp 5.84%, Toxocara spp 0.24%, Isospora spp 42.38%; and Ancylostoma spp 54.8%, Dipylidium spp 8%, Strongylus spp 4%, Trichuris spp 3.2%, and isospora spp 30% were identified in females. Regarding the prevalence of ectoparasites, there are 60% of canines with ectoparasites, which corresponds to 119 canines and 40% without ectoparasites, which corresponds to 81 canines, in the same way, it was classified by age groups. It was found that in puppies there is the presence of Ctenocephalides spp 87.38%, Trichodectes spp 7.74%, Demodex spp 4.86%; In adults Ctenocephalides spp 73.54%, Trichodectes spp 16.77%, Demodex spp 9.67% and finally in geriatric was found Ctenocephalides spp 72.31%, Trichodectes spp 20.58%, Demodex spp 7.10%; in the prevalence of ectoparasites according to the sex of the canines, where Ctenocephalides spp was identified in males 75.38%, Trichodectes canis 18.13%, Demodex spp 6.48% and in females were found Ctenocephalides spp 81.45%, Trichodectes canis 11.55%, Demodex canis 6.99%. According to the results obtained, it is necessary to implement health education actions to the community and the development of deworming campaigns for the canines, a correct management of the environment and feeding of the canines that live with the inhabitants of the community.